Review of Hooke and Jeeves Direct Search Solution M ethod Analysis Applicable To Mechanical Design Engineering - Mr. G.S KIRGAT; Prof. A.N Surde (International Journal of Innovations in Engineering Research and Technology, 2021)
Role of optimization in engineering design is prominent one with the advent of computers. Optimization hasbecome a part of computer aided design methodology. It is primarilybeing used in those design activities inwhich the goal is not only to achieve a feasible design, but also a design objective. The paper reviews theoptimization in detail followed by the literature review and brief discussion of Hooks and Jeeves MethodAnalysis with an example.